REGIONAL DUTOR TRADITIONS OF UZBEKISTAN FERGANA, BUKHARA, AND KHOREZM (Web of Teachers: Inderscience Research, 2025)
This study examines the regional differentiation of dutor performance traditions in Uzbekistan by conducting a systematic comparative analysis of the Fergana, Bukhara, and Khorezm schools. Through the evaluation of stylistic parameters, performance techniques, repertoire sources, and transmission mechanisms, the article identifies both shared structural foundations and distinctive regional characteristics. The findings demonstrate that, although the three schools originate from a common national musical framework, each has developed unique aesthetic priorities and technical principles shaped by historical, cultural, and socio-musical factors. The research emphasizes the necessity of further documentation, pedagogical standardization, and preservation strategies to ensure the continuity of this orally transmitted musical heritage.